دور الحماية الدبلوماسية في حماية حقوق الإنسان - مروى دلهوم; رندة مشري (My University, 2021)
Summary : The guarantee of human rights is fundamental in the international community, since the violation of an individual's right is an affront to the very existence of the State. However, it does not allow him to resort to the bodies of the host State until he has met a number of conditions. in addition to its exhaustion of all domestic legal means, and in order to obtain adequate compensation for damage , the State party should address all the judicial and administrative sections available to it in this State, To obtain appropriate compensation for damage, In the absence of reparation for the injury suffered, the State of which he is a national shall take the necessary action to confront the injured State and require it to repair the injury, whether through diplomatic or judicial action, through which the State shall demand that the injury inflicted on its nationals be repaired. This is known as diplomatic protection, which is necessary and important for the protection of human rights. ................... ملخص : إن ضمان حقوق الانسان يعد من الأمور الأساسية في المجتمع الدولي ، فبانتهاك حق من حقوق الفرد يعد مساسا بكيان الدولة ذاتيا ، إلا أنه لا يسمح له باللجوء إلى هيئات الدولة المضيفة إلا بعد أن تتوفر فيه مجموعة من الشروط ، بالإضافة إلى استنفاذه لكافة الطرق والسبل القانونية الداخلية وان يطرق كافة الابواب القضائية والادارية المتاحة امامه في هذه الدولة للحصول على التعويض المناسب لجبر الضرر، و في حال لم تقم بجبر الضرر الواقع عليه تقوم الدولة التي يحمل جنسيتها باتخاذ الاجراءات اللازمة لمواجهة الدولة المرتكبة للضرر ومطالبتها بإصلاحه، سواء عن طريق اتخاذ الاجراءات الدبلوماسية أو القضائية و التي من خلالها تطالب فيها الدولة بإصلاح الضرر الواقع على رعاياها . وهذا ما يعرف بالحماية الدبلوماسية و التي تعتبر أمر ضروري و مهم لحماية حقوق الانسان. ..................... Résumé : Garantir les droits de l’homme est fondamental dans la communauté internationale. la violation du droit d’un individu est préjudiciable à l’entité de l’État lui-même, mais il n’est pas autorisé à recourir à des organes de l’État hôte tant qu’il ne remplit pas un ensemble de conditions. En plus d’épuiser toutes les méthodes et méthodes juridiques nationales, et de répondre à toutes les questions judiciaires et administratives disponibles dans cet État afin d’obtenir une indemnisation adéquate pour le dommage, Dans le cas où il ne parvient pas à réparer le dommage subi, l’État dont il est ressortissant prend les mesures nécessaires pour confronter l’État qui a commis le préjudice et en exiger réparation. en prenant des mesures diplomatiques ou judiciaires par lesquelles un État est tenu de remédier au préjudice infligé à ses ressortissants. C’est ce qu’on appelle la protection diplomatique, qui est essentielle et importante pour la protection des droits de la personne.